Challenges faced by University of Zimbabwe social work students on fieldwork attachment - Muchinako, George Alex; Muridzo, Noel G. (Researchjournali International Publishing House, 2020)
The profession of social work promotes the welfare of human beings and the betterment of human society through the development and systematic application of scientific knowledge of societal activities and services. This knowledge is acquired through social work education and training which is done in two components, one academic and the other, practical (fieldwork).This study was on the challenges faced by student social workers in and around the fieldwork process. A survey using a self administered questionnaire was used to collect information. The students reported facing challenges that included difficulty in securing places to do fieldwork, resource constraints, limited duration of time for fieldwork, lack of trained social work supervisors at some agencies and lack of computer skills to use in writing reports and processing information. Given that fieldwork is a critical component in social work training, the paper notes that it is important that it is done properly and makes recommendations to improve the situation to enable students to make the best on the fieldwork training.